Another layer of complexity in Staphylococcus aureus methionine biosynthesis control: unusual RNase III-driven T-box riboswitch cleavage determines met operon mRNA stability and decay. Issue 4 (15th January 2021) - Wencker, Freya D R; Marincola, Gabriella; Schoenfelder, Sonja M K; Maaß, Sandra; Becher, Dörte; Ziebuhr, Wilma
Abstract: In Staphylococcus aureus, de novo methionine biosynthesis is regulated by a unique hierarchical pathway involving stringent-response controlled CodY repression in combination with a T-box riboswitch and RNA decay. The T-box riboswitch residing in the 5′ untranslated region ( met leader RNA) of the S. aureus metICFE-mdh operon controls downstream gene transcription upon interaction with uncharged methionyl-tRNA. met leader and metICFE-mdh (m)RNAs undergo RNase-mediated degradation in a process whose molecular details are poorly understood. Here we determined the secondary structure of the met leader RNA and found the element to harbor, beyond other conserved T-box riboswitch structural features, a terminator helix which is target for RNase III endoribonucleolytic cleavage. As the terminator is a thermodynamically highly stable structure, it also forms posttranscriptionally in met leader/ metICFE-mdh read-through transcripts. Cleavage by RNase III releases the met leader from metICFE-mdh mRNA and initiates RNase J-mediated degradation of the mRNA from the 5′-end. Of note, metICFE-mdh mRNA stability varies over the length of the transcript with a longer lifespan towards the 3′-end. The obtained data suggest that coordinated RNA decay represents another checkpoint in a complex regulatory network that adjusts costly methionine biosynthesis to current metabolic requirements. Graphical Abstract: